Enhancing the climate, peace, and security nexus in Northern and Northeastern Kenya - Ali, Halimo; Hajir, Maryam; Kenduiywo, Benson; Belli, Anna; Hussein, Hasfa; Pacillo, Grazia (2024)
This policy brief emphasizes the need to integrate peacebuilding into climate-smart programs, showcasing models where climate interventions also foster peace. It identifies weaknesses in separating climate and security efforts and offers recommendations to enhance funding for integrated climate, peace, and security initiatives.